Social reproduction theory revisited. Issue 7 (3rd October 2021) - Backer, David I.; Cairns, Kate
Abstract: Social reproduction theory names at least two distinct traditions, one of which has a long history in educational research. Social reproduction theory in education emerged out of a concern with education's relationship to capitalist inequalities. By contrast, social reproduction feminism developed out of feminist interventions regarding the role of women's unpaid care-work in the reproduction of capitalism. In this paper, we suggest that the renewed energy surrounding social reproduction feminism provides an opportunity to revisit social reproduction theorizing in education. We review the fields' histories and ready the ground for an integrated framework. At the heart of this integration is a feminist analysis of reproductive labor in its contradictory relationship to capitalism. Expanding the analysis from the reproduction of capitalist relations to the reproduction of life under capitalism, this approach avoids the pitfalls of determinism and attends to students' participation and teachers' work in the contested labor of social reproduction.